A randomized double-blind clinical trial of posterior composite restorations with or without bevel: 1-year follow-up - Fábio Herrmann Coelho-; Junara Cristina Camargo; Tiago Beskow; Matheus Dalmolin Balestrin; Celso Afonso Klein-Júnior; Flávio Fernando Demarco (University of São Paulo, 2012)
OBJECTIVE: This randomized double-blind clinical trial compared the performance of posterior composite restorations with or without bevel, after 1-year follow-up. MATERIAL AND METHODS: Thirteen volunteers requiring at least two posterior composite restorations were selected. Twenty-nine cavities were performed, comprising 14 without bevel (butt joint) and 15 with bevel preparation of the enamel cavosurface angle. All cavities were restored with simplified adhesive system (Adper Single Bond) and composite resin (Filtek P60). A halogen light curing unit was used through the study. Restorations were polished immediately. Analysis was carried out at baseline, after 6 months and after 1 year by a calibrated evaluator (Kappa), according to the FDI criteria. Data were statistically analyzed by Mann-Whitney test (p <0.05). RESULTS: Beveled and non-beveled cavities performed similarly after 1 year follow-up, regarding to fractures and retention, marginal adaptation, postoperative hypersensitivity, recurrence of caries, surface luster and anatomic form. However, for surface and marginal staining, beveled cavities showed significantly better performance (p<0.05) than butt joint restorations. CONCLUSIONS: It was concluded that the restorations were acceptable after 1 year, but restorations placed in cavities with marginal beveling showed less marginal staining than those placed in non-beveled cavities.